Culdoscopy for general surgeons and gynecologists - Tsin, Daniel A. (Endoskopska revija, 2007)
Culdoscopy is a form of Natural Orifice Translumenal Endoscopic Surgery (NOTES), used for diagnostic and selected operative gynecological procedures. Advances in flexible technology will render major intraabdominal operations possible. Minilaparoscopy Assisted Natural Orifice Surgery (MANOS) is a synergetic combination of operative culdoscopy and minilaparoscopy for major surgery, and consitutes an easy evolutionary step for experienced laparoscopists.
Keywords: endoskopska kirurgija; kuldoskopija; medicinski instrumenti